Analysis of Psychological Personality Factors in Learning English for College Sports Students - Chunhui Liu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
China has a fascinating history and culture about the sports industry. Each year, the worth of China's sports industry increases. Using a wide range of samples taken from various districts in China, the studies and literature connected to this show a close relationship Analysis of Psychological Personality Factors in Learning English for College Sports Students. China had sent a single athlete to the Olympic Games in 1932, which drew worldwide attention, but no substantial revenue was earned. The growth of China's sports business has given non-sports and sports groups, both worldwide and nationally, a huge opportunity. Sports improve children's physical and mental strength. It can help a child develop organizational skills by ensuring that they attend training team meetings and many days on time, are determined to succeed until they achieve their best academic leadership, and respect the judgment of the umpire or judge. The data was collected from 60 sports players and analyzed by using SEM PLS 3. To analyze the sports and culture in Chine, this study has incorporated the Sports Culture as an Independent Variable and Socioeconomic Status of China as a dependent variable. Whereas, Sports Participants is used as Mediating Variable. Whereas, the results indicated a significant association between the variables.